The Discovery of Novel Experimental Therapies for Inflammatory Arthritis - Charles J. Malemud (Mediators of Inflammation)
Conventional and biologic disease-modifying antirheumatic drugs have revolutionized the medical therapy of inflammatory arthritis. However, it remains unclear as to what can be done to treat immune-mediated chronic inflammation after patients become refractory to these therapies or develop serious side-effects and/or infections forcing drug withdrawal. Because of these concerns it is imperative that novel targets be continuously identified and experimental strategies designed to test potential arthritis interventions in vitro, but more importantly, in well-validated animal models of inflammatory arthritis. Over the past few years, sphingosine-1-phosphate, interleukin-7 receptor, spleen tyrosine kinase, extracellular signal-regulated kinase, mitogen-activated protein kinase 5/p38 kinase regulated/activated protein kinase, micro-RNAs, tumor necrosis factor-related apoptosis inducing ligand and the polyubiquitin-proteasome pathway were identified as promising novel targets for potential antiarthritis drug development. Indeed several experimental compounds alter the biological activity of these targets and have shown clinical efficacy in animal models of arthritis. A few of them have even entered the first phase of human clinical trials.